KAHIYANG NUR ANDIFA IN HER FIRST LANGUAGE ACQUISITION - Diyan Andriani (Journal Of Language Education and Development (JLed), 2019)
This study aims to find out how much vocabulary is produced by children aged 20 months. The participants were the daughters of their own researcher named Kahiyang Nur Andifa on the grounds that researchers would easily obtain data. The methodology of this research is descriptive qualitative. Techniques in data collection, researchers use recording tools and records. The results of this study can be concluded that Kahiyang can produce 187 words, clauses and can producesimple sentences in his conversations with people around.